Corrupção e religiosidade: uma análise cross-country mediada pela qualidade da contabilidade - Santos, Simone Miranda dos (2021)
Corruption, in general, involves monetary pay, therefore it requires accounting manipulation to conceal the transactions. It is possible the management’s decision to allow these manipulations is influenced by religiousness. This research, based on the Social Norms Theory, considers religiousness a factor capable of influencing the management’s decisions regarding quality of the accounting and the corruption. This study had the goal of identifying the association between religiousness and corruption, mediated by the quality of the accounting. The sample for this research includes 36 countries, and the processing of the data collected from 2010 to 2014 was done using Partial Least Squares Path Modeling. The study’s results show that more intense religiousness is associated with lower-quality accounting, and together they are associated with more corruption. It is likely that collectivism, a common feature of highly religious environments, favors the development of collusions, which may harm the quality of the accounting and facilitate the emergence of corruption. Besides, more religious environments are associated with less surveillance, which encourages the manipulation of accounting information and corruption. The results contribute to the literature by demonstrating that the combined effect of religiousness and quality of accounting in combating corruption was not efficient. The evidences from this study also allows us to assess the influence of religiousness in the management’s decisions, acting like a social norm, with repercussions in the quality of accounting and corruption.